Aquifer Characterization and Uncertainty in Multi‐Frequency Oscillatory Flow Tests: Approach and Insights. Issue 2 (27th September 2021) - Patterson, Jeremy R.; Cardiff, Michael
Abstract: Characterizing aquifer properties and their associated uncertainty remains a fundamental challenge in hydrogeology. Recent studies demonstrate the use of oscillatory flow interference testing to characterize effective aquifer flow properties. These characterization efforts relate the relative amplitude and phase of an observation signal with a single frequency component to aquifer diffusivity and transmissivity. Here, we present a generalized workflow that relates extracted Fourier coefficients for observation signals with single and multiple frequency components to aquifer flow properties and their associated uncertainty. Through synthetic analytical modeling we show that multi‐frequency oscillatory flow interference testing adds information that improves inversion performance and decreases parameter uncertainty. We show increased observation signal length, sampling frequency, and pressure sensor accuracy all produce decreased parameter uncertainty. This work represents the first attempt we are aware of to quantify effective aquifer parameters and their associated uncertainty using multi‐frequency oscillatory flow interference testing. Abstract : Article Impact Statement : Multi‐frequency analysis under oscillatory flow conditions improves effective parameter estimates and reduces parameter uncertainty.